Psychometric properties of the Lithuanian version of the functionality appreciation scale - Migle Baceviciene; Vaiva Balciuniene; Rasa Jankauskiene (Scientific Reports)
Abstract This study aimed to assess the psychometric properties of the Lithuanian translation of the Functionality Appreciation Scale (FAS). A sample (n = 759) of adults (424 women and 335 men; mean age 23.2 ± 7.1 and age range 18–44 years) participated in the cross-sectional study. Body functionality appreciation, body appreciation, self-esteem, disordered eating and physical activity habits were assessed. Exploratory factor analysis (EFA; n = 379) identified a unidimensional factor structure of FAS, supported by findings in a second split-subsample using confirmatory factor analysis (CFA, n = 380). FAS scores were invariant across gender groups. No mean score differences were observed between genders. Composite reliability of FAS was established in women (ω = 0.94, 95% CI = 0.92, 0.95) and men (ω = 0.92, 95% CI = 0.90, 0.94). Positive associations of FAS with body appreciation, self-esteem and physical activity habits and negative relationships with disordered eating and BMI (in women) confirmed construct validity. FAS predicted self-esteem over and above the variance accounted for by other study measures. The Lithuanian version of FAS is a psychometrically sound measure of body functionality appreciation. FAS might contribute to a comprehensive assessment of positive body image and can be used in various interventions.